2014
DOI: 10.12659/msm.890031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ranibizumab treatment on the extracellular matrix in patients with neovascular age-related macular degeneration

Abstract: BackgroundWe know the influence of the intravitreal anti-vascular endothelial growth factor (VEGF) injections on the choroidal neovascularization in the course of exudative age-related macular degeneration (AMD). However, the influence of the ranibizumab therapy in question on the extracellular matrix (ECM) remains unknown. We aimed to estimate the influence of Lucentis intravitreal injections on the gene expression of structural components of the extracellular matrix in patients with neovascular AMD.Material/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…ECM is a highly dynamic composition of vasculature [ 6 ]. Collagen is the most abundant protein in the ECM [ 7 ]. It has been shown that accumulation of ECM is one of the most notable pathologic changes across the vascular wall in pulmonary hypertension [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…ECM is a highly dynamic composition of vasculature [ 6 ]. Collagen is the most abundant protein in the ECM [ 7 ]. It has been shown that accumulation of ECM is one of the most notable pathologic changes across the vascular wall in pulmonary hypertension [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Age-related macular degeneration (AMD) is the main cause of practical and irreversible central blindness in patients after the age of 50 years [ 5 , 6 ]. Neovascular age-related macular degeneration, also known as exudative AMD, has a long natural course that involves repeated haemorrhages in the macular area and a poor prognosis in terms of visual acuity.…”
Section: Discussionmentioning
confidence: 99%